Finding a needle in a haystack: an interactive video archive explorer for professional video searchers - Haesen, Mieke; Meskens, Jan; Luyten, Kris; Coninx, Karin; Becker, Jan Hendrik; Tuytelaars, Tinne; Poulisse, Gert-Jan; Pham, Phi The; Moens, Marie-Francine (Multimedia tools and applications, 2013)
Professional video searchers typically have to search for particular video fragments in a vast video archive that contains many hours of video data. Without having the right video archive exploration tools, this is a difficult and time consuming task that induces hours of video skimming. We propose the video archive explorer, a video exploration tool that provides visual representations of automatically detected concepts to facilitate individual and collaborative video search tasks. This video archive explorer is developed by employing a user-centred methodology, which ensures that the tool is more likely to fit to the end user needs. A qualitative evaluation with professional video searchers shows that the combination of automatic video indexing, interactive visualisations and user-centred design can result in an increased usability, user satisfaction and productivity.